II Encontro Nacional de Ensino de Paisagismo em Escolas de Arquitetura e Urbanismo no Brasil - Macedo, Silvio Soares (Paisagem e Ambiente, 1995)
This paper focuses the development of the II National Seminary of Landscape professours in the Brazilian Architecture and Urban Schools, wich took place in São Paulo at the Faculdade de Arquitetura e Urbanismo da USP in October 1995. It presents a synthesis of this process and the main conclusions of the seminar